Pengaruh Lingkungan Belajar Terhadap Prestasi Belajar Mahasiswa Jurusan Pendidikan Agama Islam - Irma (el-Idarah: Jurnal Manajemen Pendidikan Islam, 2019)
This research discuss some problems, they are: (1) How does learning environment of Islamic education student?, (2) How does learning achievement of Islamic Education Department student? And (3) Are there any influences between learning environment toward learning achievement of Islamic Education Department student? Population of this research is student of Islamic Education Department 2014 Tarbiyah and Teaching Faculty of Alauddin State Islamic University of Makassar, there are 194 people. In proportionally sampling 15% with sample taking technique, random sampling so that got sample 30 people. Data collecting technique in this research such as questionnaire and document, so that got the data that analyzed using descriptive statiscs technique. The result of this research showed that student learning environment of Islamic Education Department 2014 Tarbiyah and Teaching Faculty of Alauddin State Islamic University of Makassar, getting score 65 (good) because in interval 60-66 that adequate category and student learning achievement of Islamic Education Department 2014 Tarbiyah and Teaching Faculty of Alauddin State Islamic University of Makassar, getting score 3,59 in interval 3,51-3,75 in very good category. The result of hypotheses test that t0= 34.39796 and ttable= 2.048 where is t0 > ttable so that H0 rejected Ha accepted. So that, from this research can be concluded that student learning environment influence to student learning achievement Islamic Education Department 2014 Tarbiyah and Teaching Faculty of Alauddin State Islamic University of Makassar.